# Composite Mapping is Mapping

Jump to navigation
Jump to search

## Theorem

Let $S_1, S_2, S_3$ be sets.

Let $f: S_1 \to S_2$ and $g: S_2 \to S_3$ be mappings.

Then the composite mapping $g \circ f$ is also a mapping.

## Proof

The composite of $f$ and $g$ is defined as:

- $g \circ f := \set {\tuple {x, z} \in S_1 \times S_3: \exists y \in S_2: \tuple {x, y} \in f \land \tuple {y, z} \in g}$

It is necessary to show that $g \circ f$ is both left-total and many-to-one.

### Left-total

From the definition of a mapping:

\(\displaystyle \forall x \in S_1: \exists y \in S_2: \ \ \) | \(\displaystyle \map f x\) | \(=\) | \(\displaystyle y\) | Definition of Mapping | |||||||||

\(\displaystyle \forall y \in S_2: \exists z \in S_2: \ \ \) | \(\displaystyle \map g y\) | \(=\) | \(\displaystyle z\) | Definition of Mapping | |||||||||

\(\displaystyle \implies \ \ \) | \(\displaystyle \forall x \in S_1: \exists z \in S_3: \ \ \) | \(\displaystyle \map g {\map f x}\) | \(=\) | \(\displaystyle z\) | |||||||||

\(\displaystyle \implies \ \ \) | \(\displaystyle \forall x \in S_1: \exists z \in S_3: \ \ \) | \(\displaystyle \map {g \circ f} x\) | \(=\) | \(\displaystyle z\) | Definition of Composite Mapping |

That is, $g \circ f$ is left-total.

$\Box$

### Many-to-one

Suppose $x_1, x_2 \in S_1: x_1 = x_2$.

Then as $f$ is a mapping and so by definition many-to-one:

- $\map f {x_1} = \map f {x_2}$

and so:

- $\map g {\map f {x_1} } = \map g {\map f {x_2} }$

demonstrating that $g \circ f$ is similarly many-to-one.

$\blacksquare$

## Sources

- 1955: John L. Kelley:
*General Topology*... (previous) ... (next): Chapter $0$: Functions - 1977: Gary Chartrand:
*Introductory Graph Theory*... (previous) ... (next): Appendix $\text{A}.4$: Functions